US Energy and Climate Legislation – The Big Deal - Robinson, D (Oxford Institute for Energy Studies, 2009)
US energy and climate change legislation will have a powerful influence on any global agreement replacing the Kyoto Protocol when it expires in 2012. Dr. David Robinson analyzes draft US legislation (specifically the Waxman Markey Bill) and argues that it will fail to promote an early transition to a low carbon economy mainly due to its exaggerated efforts to smooth the transition for the coal industry and its customers. He proposes amendments to the draft legislation.